Papua New Guinea : Sanitation, Water Supply and Hygiene in Urban Informal Settlements - World Bank Group (Washington, DC, 2014)
In 2012 Papua New Guinea undertook a national Service Delivery Assessment of rural water, rural sanitation, urban water and urban sanitation services to identify coverage and targets, how well services are being delivered and the financing shortfalls in these subsectors. Immediately following this assessment, stakeholders, through a national policy task force, have developed a draft of the country s first National Water, Sanitation and Hygiene (WASH) Policy. During the course of the assessment and policy development, peri-urban and informal settlements have been consistently identified as areas which are underserviced and overlooked for water and sanitation services. The need to provide affordable and appropriate services in settlements, as well as improve health and living conditions, was highlighted. Amongst stakeholders, it was agreed that baseline information on WASH conditions in settlements was needed in order to develop strategies and to respond appropriately to needs of settlements in the future. Previous settlement research has focused on urbanization, housing ownership, land issues, employment, and anthropology, but WASH has not been researched specifically or in depth. Therefore in 2014, the Water and Sanitation Program of the World Bank (WSP), together with key stakeholders, conducted research in informal settlements in the capital Port Moresby and a representative provincial town (Wewak) to understand the conditions, aspirations, barriers and opportunities to improve water, sanitation and hygiene for informal settlers.